Development of Diubiquitin‐Based FRET Probes To Quantify Ubiquitin Linkage Specificity of Deubiquitinating Enzymes. (21st March 2016) - Geurink, Paul P.; van Tol, Bianca D. M.; van Dalen, Duco; Brundel, Paul J. G.; Mevissen, Tycho E. T.; Pruneda, Jonathan N.; Elliott, Paul R.; van Tilburg, Gabriëlle B. A.; Komander, David; Ovaa, Huib
Abstract: Deubiquitinating enzymes (DUBs) are proteases that fulfill crucial roles in the ubiquitin (Ub) system, by deconjugation of Ub from its targets and disassembly of polyUb chains. The specificity of a DUB towards one of the polyUb chain linkages largely determines the ultimate signaling function. We present a novel set of diubiquitin FRET probes, comprising all seven isopeptide linkages, for the absolute quantification of chain cleavage specificity of DUBs by means of Michaelis–Menten kinetics. Each probe is equipped with a FRET pair consisting of Rhodamine110 and tetramethylrhodamine to allow the fully synthetic preparation of the probes by SPPS and NCL. Our synthetic strategy includes the introduction of N, N′ ‐Boc‐protected 5‐carboxyrhodamine as a convenient building block in peptide chemistry. We demonstrate the value of our probes by quantifying the linkage specificities of a panel of nine DUBs in a high‐throughput manner. Abstract : The magnificent seven : All seven isopeptide‐linked diubiquitin conjugates equipped with a Rhodamine‐TAMRA FRET pair were prepared. The synthesis includes the use of a highly convenient N, N′ ‐Boc‐protected Rhodamine building block. These probes enable the absolute quantification of the ubiquitin linkage specificity of deubiquitinating enzymes by means of Michaelis–Menten kinetics.